Prospective evaluation of morbidity in patients who underwent autogenous bone-graft harvesting from the mandibular symphysis and retromolar regions - Pereira, Rodrigo Santos [UNESP]; Pavelski, Maicon D.; Griza, Geraldo L.; Boos, Fernanda B. J. D. [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (Wiley, 2019)
Background: Autogenous bone grafts are the most favorable and predictable types of bone graft due to their osteogenic, osteoinductive, and osteoconductive properties. The advantages of harvesting from mandibular bone are that it requires only local anesthesia, is less invasive, has less morbidity, and avoids harvesting from distant sites, thus making it the best choice for maxillary bone reconstruction. Purpose: The aim of this study was to evaluate inferior alveolar nerve (IAN) neurosensory disturbances after autogenous bone graft harvesting from the mandibular symphysis and retromolar region to reconstruct maxillary sinus height for posterior dental implant placement and the effect of these disturbances on patient satisfaction. Materials and Methods: Fifty-four patients were invited to participate in this study. Autogenous bone graft was harvested from the mandibular symphysis and retromolar regions. After the procedure, the patients were evaluated by means of an adapted questionnaire to determine if they had complaints of neurosensory disturbances at the following time intervals: immediately, 1, 2-5, 6, 7-11, and 12 months postsurgery. Results: Immediately after surgery, 28 patients described sensory changes and 25 reported paresthesia of inferior lip. Only three patients reported pain, and one patient experienced dental hypersensitivity after the surgical procedure. During the evaluation period, the patients reported a decrease in paresthesia and a return of sensation to areas innervated by the IAN. After 12 months, five patients still reported paresthesia of areas innervated by the IAN. Beside this, patients reported significant clinical improvement from the beginning of the evaluation, as 49 patients were satisfied with their treatment outcomes. Conclusion: Harvesting bone grafts from the mandibular symphysis results in greater postoperative morbidity upon immediate evaluation compared with bone graft harvesting from the retromolar region. Nevertheless, during clinical follow-up, the results of both treatments showed that sensation was eventually recovered, depending on the healing period.